1985
DOI: 10.1017/s0033583500000366
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of electron-transfer proteins at electrodes

Abstract: Studies of electron-transfer reactions of redox proteins have, in recent years, attracted widespread interest and attention. Progress has been evident from both physical and biological standpoints, with the increasing availability of three-dimensional structural data for many small electron-transfer proteins prompting a variety of systematic investigations (Isied, 1985). Most recently, attention has been directed towards questions concerning the elementary transfer of electrons between spatially remote redox s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(52 citation statements)
references
References 114 publications
(94 reference statements)
3
49
0
Order By: Relevance
“…The term ⌬G* comprises contributions from aqueous solvent hydration shell reorganization energies. k el varies exponentially with r(Å), the distance separating the donor and acceptor molecules; for r ϭ 12 Å, k el has been predicted to be 6 ϫ 10 Ϫ6 (43). From the FRET experiments reported above, the experimental value for the distance between the galactosyl moiety of GalCer and the lectin binding site of gp41 is Ͻ15 Å.…”
Section: Computation Of the Free Energy Of Activation Of The Electronmentioning
confidence: 98%
“…The term ⌬G* comprises contributions from aqueous solvent hydration shell reorganization energies. k el varies exponentially with r(Å), the distance separating the donor and acceptor molecules; for r ϭ 12 Å, k el has been predicted to be 6 ϫ 10 Ϫ6 (43). From the FRET experiments reported above, the experimental value for the distance between the galactosyl moiety of GalCer and the lectin binding site of gp41 is Ͻ15 Å.…”
Section: Computation Of the Free Energy Of Activation Of The Electronmentioning
confidence: 98%
“…Cyclic voltammetry at a viologenmodified glassy carbon electrode showed a quasi-reversible response around Em = -367 mV. Van Dijk et al concluded this finding to reflect direct electrochemistry of the ferredoxin [32]; however, Armstrong et al have suggested surface mediation as an alternative interpretation [2].…”
Section: Direct Responses Of Other Redox Proteins At Bare Glassy Carbonmentioning
confidence: 99%
“…The methodological hows and whys appear to a considerable extent to have been established by now in studies employing small, electron-transferring proteins [2]. The first successful detection of electron transfer between a true enzyme and a solid electrode was recently reported [3].…”
mentioning
confidence: 99%
“…The strong interest in this small soluble haem protein is, on the one hand, related to its important physiological functions in the respiratory chain of aerobic organisms and in apoptotic pathways [1][2][3][4]. On the other hand, owing to its small size, its well-characterised structural and spectral properties as well as the availability of engineered protein variants, cytochrome c is frequently used as model protein for studying fundamental biophysical processes such as electron transfer [5][6][7][8][9] and protein folding [10][11][12][13][14][15][16][17]. Specifically, the elucidation of relationships between protein folds and dynamics and the electron transfer properties is of particular interest in view of its impact for understanding biological processes on a molecular level and for the design of novel tailor-made redox enzymes for potential biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%